2011
DOI: 10.1039/c1ob05067b
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenolates: metallated polyhydroxylated fullerenes with potent anti-amyloid activity

Abstract: It has been revealed for the first time that sodium fullerenolate Na 4 [C 60 (OH)~3 0 ] (NaFL), a water soluble polyhydroxylated [60]fullerene derivative, destroys amyloid fibrils of the Ab(1-42) peptide in the brain and prevents their formation in in vitro experiments. The cytotoxicity of NaFL was found to be negligibly low with respect to nine different culture cell lines. At the same time, NaFL showed a very low acute toxicity in vivo. The maximal tolerable dose (MTD) and LD50 for NaFL correspond to 1000 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…22 Assuming these time frames are similar in humans, C60 fullerene may not benefit envenomations resulting in extremely rapid death, but it could provide therapeutic potential for the sizeable percentage of snakebite cases in which the patient survives beyond these times. With a half-life of 48 22 but further study will be needed to confirm its safety in humans.…”
Section: Discussionmentioning
confidence: 96%
“…22 Assuming these time frames are similar in humans, C60 fullerene may not benefit envenomations resulting in extremely rapid death, but it could provide therapeutic potential for the sizeable percentage of snakebite cases in which the patient survives beyond these times. With a half-life of 48 22 but further study will be needed to confirm its safety in humans.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier we have shown that fullerene C 60 and a number of its derivatives are capable of destroying amyloid fibrils of brain Aβ(1-42) peptide, participat ing in the pathogenesis of Alzheimer's disease, and also muscle X protein [17][18][19][20][21]. From the obtained results a conclusion has been made that fullerene C 60 and its derivatives may be regarded as potential anti amyloid preparations.…”
Section: Introductionmentioning
confidence: 83%
“…It has been shown that 1,2 (dimethoxymeth ano)fullerene is capable of inhibiting early stages of aggregation of Aβ(1-40) and Aβ (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) peptides of the brain, specifically binding with the central hydro phobic motif KLVFF (Lys Leu Val Phe Phe) of Aβ peptides [16].…”
Section: Introductionmentioning
confidence: 99%
“…This protective effect was observed both at early stage (day 14) of Аβ25-35-induced neurotoxicity and much later, on day 45. Fullerenes are well known to be characterized by their powerfully expressed antioxidant and antiamyloid activities [10], [11], [58], [59], [60]. Recently, we have shown that intrahippocampal injection of C60HyFn was able to protect both the mechanisms of peptide synthesis and amyloid accumulation, and CA1 neurons in rats from neurotoxic effects of the intracerebral injection of Аβ25-35 [17].…”
Section: Discussionmentioning
confidence: 99%